Grocery consumer relational perceptions in green consumption context - Marta Fernandes Gonçalves; João Menezes; Catarina Marques (Tourism & Management Studies)
An exchange perspective of the relationship customer-grocery recognizes the important role that both the seller and the shopper assume in their relationships. Today consumers are increasingly considering green consumption, which has led to a situation where retailers expend substantial resources in response to this challenge. However, this consumption has remained lackluster justifying the need for greater knowledge about consumers’ behaviour. The purpose of this paper is to characterize groups of customers based on their perceptions of value, satisfaction with retailers as well as on risk perceived associated with their environmentally consumption practices. As a result of cluster analysis, we obtained a consumers’ typology differing in their relational benefits, satisfaction and risks perceptions. Some suggestions are given to retailers and also recommendations about the need to closely consider their product offerings to ascertain what aspects contribute to the value considered by shoppers.